Pengaruh Ekstrak Etanol Teh Hijau (Camellia Sinensis) terhadap Pertumbuhan Bakteri Staphylococcus Epidermidis - Isramilda Isramilda; Malahayati Rusli Bintang; Foreandri Bakti Syafeli (Universitas Batam, 2022)
Background: Staphylococcus epidermidis is a polluting bacterium, normal flora in its natural habitat, but can cause infection in other habitats, especially if the immune systems is weak. The purpose of this study was to determine the effect of green tea (Camellia sinensis) ethanol extract on the growth of Staphylococcus epidermidis. Methods: This research is an experimental research with 25 cultures of Staphylococcus epidermidis were divided into five groups. For the first treatment group (negative control), distilled water was given; the second treatment group (positive control), chloramphenicol was given; the third treatment group (comparison group) green tea ethanol extract with 55% concentration; the fourth treatment group green tea ethanol extract with 65% concentration; the fifth treatment group green tea ethanol extract with 75 % concentration. After that, the diameter of the inhibition zone was calculated. Data relating to the inhibition zone were analyzed statistically. Results were analyzed by using the Kruskal Wallis test followed by a Post Hoc Man Whitney test in order to determine differences between the treatment groups. Results: The results showed that, the ethanol extract of green tea (Camellia sinensis) inhibited Staphylococcus epidermidis bacteria at a concentration of 65%. Conclusion: Based on the results of this study, it can be concluded that green tea (Camellia sinensis) ethanol extract inhibits Staphylococcus epidermidis growth.